Evidence-informed stakeholder consultations to promote rights-based approaches for children with disabilities - Shikako, Keiko; Lai, Jonathan; Yoo, Paul Y.; Teachman, Gail; Majnemer, Annette (Frontiers in Rehabilitation Sciences, 2024)
Purpose To strengthen the translation of evidence to actionable policy, stakeholder engagement is necessary to synthesize, prioritize and contextualize the academic research content into accessible language. In this manuscript we describe a multi-level evidence-based stakeholder consultation process and related outcomes proposed to promote awareness of and foster cross-sectorial collaborations towards human rights-based approaches for children with disabilities. Methods Mixed-methods participatory action research done in three steps: (1) A literature review of peer-reviewed evidence on rights-based approaches in childhood disabilities; (2) Consultation with researchers in diverse fields, grassroot organizations, caregivers, and youth with disabilities; (3) A constructive dialogue with decision makers at federal and provincial levels in Canada to discuss consultations results. Results Stakeholders value human rights approaches that can have a direct impact on practical aspects of their daily living. Organizations give high importance to adopting rights-based approaches to measure policy outcomes, while parents value service provision and youth emphasize accessibility. Conclusion The implementation of rights-based approaches in childhood disabilities can support policy, services, and daily lives of children with disabilities and the ecosystems around them. It can also guide research priorities, and create a common language to foster collaborations across sectors and interested parties.